2012
DOI: 10.1111/bjdp.12005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring early self‐referential memory effects through ownership

Abstract: The self-reference effect (SRE) is the reliable memory advantage for information encoded about self over material encoded about other people. The developmental pathway of the SRE has proved difficult to chart, because the standard SRE task is unsuitable for young children. The current inquiry was designed to address this issue using an ownership paradigm, as encoding objects in the context of self-ownership have been shown to elicit self-referential memory advantages in adults. Pairs of 4- to 6-year-old childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 56 publications
8
59
1
3
Order By: Relevance
“…People have better memory for goods that they own than goods that are owned by others, even if that ownership is simply imagined [85][86][87]. This memory bias is correlated with the activation and deactivation of brain regions involved in self-referential processing while thinking about who owns those goods [68,88].…”
Section: Psychological Ownershipmentioning
confidence: 99%
“…People have better memory for goods that they own than goods that are owned by others, even if that ownership is simply imagined [85][86][87]. This memory bias is correlated with the activation and deactivation of brain regions involved in self-referential processing while thinking about who owns those goods [68,88].…”
Section: Psychological Ownershipmentioning
confidence: 99%
“…Our findings complement this view. The self and objects associated with it may be "owned" (Cunningham, Brady-Van Den Bos, & Turk, 2011;Cunningham, Turk, Macdonald, & Macrae, 2008;Cunningham, Vergunst, Macrae, & Turk, 2012), but modesty may partially dis-own the self.…”
Section: Codamentioning
confidence: 99%
“…The SRE can be elicited through surprisingly simple self-item associations, for example by presenting to-beremembered information simultaneously with the participant's own name or face , by assigning items to self through temporary ownership (Cunningham, Turk, MacDonald, & Macrae, 2008) or through self-choice (Cunningham, van den Bos, & Turk, 2011). Several studies have also demonstrated robust SREs in early and middle childhood (Cunningham, Brebner, Quinn, & Turk, 2014;Cunningham Vergunst, Macrae, & Turk, 2013;Ross, Anderson, & Campbell, 2011;Sui & Zhu, 2005).…”
Section: The Self and Memorymentioning
confidence: 99%